Pengaruh Heavy Work Investment pada Industri E- Commerce Indonesia - Parimita, Widya; Suwatno, Suwatno; Wolor, Christian Wiradendi; Dwita, Febrisi (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024), 2024)
The rapid growth of the e-commerce industry in Indonesia shows the complexity of the relationship between personal and work factors in the context of a dynamic work environment. This research aims to assess the impact of personality and workaholism on job satisfaction through work engagement in e-commerce employees in Indonesia. This research used a quantitative method with a survey approach, and involved 210 samples of respondents from various e-commerce companies in Indonesia. A specially designed questionnaire is used to collect data regarding personality type, level of workaholism, level of work engagement, and level of employee job satisfaction. The results of data analysis show that certain personality factors, such as neuroticism, extroversion, agreeableness, conscientiousness, and openness, have a significant effect on the level of workaholism and work engagement of e-commerce employees. In addition, workaholism mediates the relationship between personality and work engagement. Job engagement, in turn, is positively related to the level of job satisfaction of e-commerce employees. These findings highlight the importance of understanding the dynamics of interactions between individual personality, workaholic behavior, work engagement, and job satisfaction in the context of the competitive e-commerce industry. The practical implications of this research include human resource management development strategies that can increase job involvement and satisfaction, while paying attention to individual personality factors and workaholic tendencies in the e-commerce work environment in Indonesia.   Keywords :  p ersonality, workaholism, job satisfaction, work engagement, e-commerce.